Sex Differences in Antidepressant Effect of Sertraline in Transgenic Mouse Models - Ma, Lei; Xu, Yong; Jiang, Wei; Li, Yuhong; Zhang, Xinzhu; Wang, Gang; Li, Rena (Frontiers in Cellular Neuroscience, 2019)
The main purpose of this study is to explore sex differences in the antidepressant effect of sertraline in genetic knockout or overexpression estrogen-synthesizing enzyme aromatase (Ar) gene mouse models in the forced swim test (FST). Our results demonstrated a significant reduction of depression-like behavior in the mice with overexpression of brain aromatase (Thy1-Ar) compared to sex- and age-matched Ar+/- mice or wild type control mice. Using HPLC analysis, we also found an association between the brain estrogen-related antidepressive behavior and the regulation of serotonin (5-HT) system. Interestingly, a single dose administration of sertraline (10mg/kg, i.p.) induced reduction of immobility time was found in all genotypes, except male Ar+/- mice. While the underlying mechanisms of sex-specific response on antidepressive effect of sertraline remain to be investigated, our data showed that female mice appear to be more sensitive to sertraline-induced changes of 5-HT system than male mice in the prefrontal cortex (PFC) and the hippocampus (HPC). Further investigation of sex-specific effect of brain estrogen on antidepressant is needed.